The Effect of Aerobic and Anaerobic Exercise on the Results of Increasing the Endurance of Tanah Laut Football Players - Arifin, Ramadhan; Hamid , Abd.; Hamid , Nurdiansyah; Hasani , Birrul; Yanur , Windi; Firdaus , Muhammad Ridayd (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Football is a sport that requires high endurance. Activities on the field that require running fast carrying the ball or chasing opponents. The need for physical endurance training to play football well. Physical training can be divided into various forms. One of these divisions is based on the use of oxygen or the dominant energy system used in an exercise, namely aerobic and anaerobic training. The research method is a quasi-experiment that the quasi-experimental method is a research method that remembers that not all variables (symptoms that appear) and experimental conditions can be given full control and to find out which variables may not be fully controlled and controlled. The Two-group pretest-posttest research design compares two aerobic and anaerobic methods. The population and sample of the study were 20 Tanah Laut soccer players. The results of the study showed that the effect of aerobic training had an impact of increasing by 8%. While anaerobic training had an impact of 5% on increasing the endurance of Tanah Laut soccer players.